The Role of Fiscal Capacity in Absorption of European Funds - Marin, Monica (Calitatea Vieții, 2014)
This paper examines the role of fiscal capacity in absorption of European funds in the country with the lowest absorption rate from EU. A special focus is placed on the key intervention area from Priority Axis on improving quality of life in rural areas (Measure 322 of Romania’s Rural National Development Plan). The units of analysis are rural municipalities of Romania, for the period of 2007–2012. Key data sources are represented by local budgets execution, official data with beneficiaries of European funds, a national census of municipalities’ access to European funds as well as a qualitative research. The study shows that the funds are concentrated on communities with low fiscal capacity. It also shows that the fiscal capacity depends on size of the organization and that of the population, but also on mayor’s political affiliation. Its importance varies between financing lines. The study sheds light on the under-researched topic of capacity of absorption of European funds focused on demand side.